2021
DOI: 10.1007/s10877-021-00756-3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic analysis of a fluid challenge with 4 ml kg−1 over 10 or 20 min: a multicenter cross-over randomized clinical trial

Abstract: Purpose A number of studies performed in the operating room evaluated the hemodynamic effects of the fluid challenge (FC), solely considering the effect before and after the infusion. Few studies have investigated the pharmacodynamic effect of the FC on hemodynamic flow and pressure variables. We designed this trial aiming at describing the pharmacodynamic profile of two different FC infusion times, of a fixed dose of 4 ml kg −1 . Methods Fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
0
13
1
1
Order By: Relevance
“…Recent studies have helped to better delineate the way a fluid challenge should be assessed, and this has important consequences regarding the techniques used for hemodynamic monitoring. Regarding the volume that should be administered, evaluating the changes in CO after administration of 4 mL/kg of crystalloids over 10 min allows the identification of the maximal number of fluid responders [ 66 ], compared to slower rates or smaller amounts of fluids [ 66 , 67 ]. Ideally, the effects of a fluid bolus should be assessed on CO or surrogates.…”
Section: How To Perform Fluid Challengementioning
confidence: 99%
“…Recent studies have helped to better delineate the way a fluid challenge should be assessed, and this has important consequences regarding the techniques used for hemodynamic monitoring. Regarding the volume that should be administered, evaluating the changes in CO after administration of 4 mL/kg of crystalloids over 10 min allows the identification of the maximal number of fluid responders [ 66 ], compared to slower rates or smaller amounts of fluids [ 66 , 67 ]. Ideally, the effects of a fluid bolus should be assessed on CO or surrogates.…”
Section: How To Perform Fluid Challengementioning
confidence: 99%
“…Our analysis and conclusions on fluid responsiveness prediction focused on the STEP-UP phase with increasing levels of pressure from 20 to 45 cmH 2 O. The STEP-DOWN phase, by prolonging the delay between the STEP-UP phase and the VE may have biased the result of the fluid responsiveness [ 26 ]. Future studies should compare the performance of a LRM at 30 cmH 2 O versus a LRM up to 45 cmH 2 O without the STEP-DOWN phase to verify our results.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, all aspects related to FC administration were investigated, showing that the amount of fluid given, the rate of administration and the threshold adopted to define fluid responsiveness impact on the final outcome of an FC [57][58][59][60][61]. A RCT showed that the duration of the administration of an FC affected the rate of fluid responsiveness, shifting from 51.0% after a 4 ml/kg FC completed in 10 min to 28.5% after an FC completed in 20 min [57].…”
Section: The Fluid Challenge Fluid Bolus and Fluid Infusion: Does The...mentioning
confidence: 99%
“…Recently, all aspects related to FC administration were investigated, showing that the amount of fluid given, the rate of administration and the threshold adopted to define fluid responsiveness impact on the final outcome of an FC [57][58][59][60][61]. A RCT showed that the duration of the administration of an FC affected the rate of fluid responsiveness, shifting from 51.0% after a 4 ml/kg FC completed in 10 min to 28.5% after an FC completed in 20 min [57]. However, this study was conducted in a limited sample of neurosurgical patients during a period of hemodynamic stability, which limits the external validity of the results in different surgical settings or in critically ill patients.…”
Section: The Fluid Challenge Fluid Bolus and Fluid Infusion: Does The...mentioning
confidence: 99%